Transurethral resection of large prostates. Issue 6171 (28th April 1979) - Marsh, D; Whitaker, R H
Abstract : A total of 102 men (mean age 70) underwent transurethral resection of the prostate. The weight of the resected prostate ranged from 40 to 152 g. Two deaths occurred in patients aged 85 and 92 years, both of whom were generally unfit. The average postoperative stay in hospital was 8.3 days. The proportions of patients with incontinence, infection, and stricture were similar to those in other series of resections and open prostatectomies, suggesting that resection of the larger prostate is safe and an acceptable alternative to an open operation.